Calcium Phosphate-Based Nanomaterials: Preparation, Multifunction, and Application for Bone Tissue Engineering - Xin Chen; Huizhang Li; Yinhua Ma; Yingying Jiang (Molecules, 2023)
Calcium phosphate is the main inorganic component of bone. Calcium phosphate-based biomaterials have demonstrated great potential in bone tissue engineering due to their superior biocompatibility, pH-responsive degradability, excellent osteoinductivity, and similar components to bone. Calcium phosphate nanomaterials have gained more and more attention for their enhanced bioactivity and better integration with host tissues. Additionally, they can also be easily functionalized with metal ions, bioactive molecules/proteins, as well as therapeutic drugs; thus, calcium phosphate-based biomaterials have been widely used in many other fields, such as drug delivery, cancer therapy, and as nanoprobes in bioimaging. Thus, the preparation methods of calcium phosphate nanomaterials were systematically reviewed, and the multifunction strategies of calcium phosphate-based biomaterials have also been comprehensively summarized. Finally, the applications and perspectives of functionalized calcium phosphate biomaterials in bone tissue engineering, including bone defect repair, bone regeneration, and drug delivery, were illustrated and discussed by presenting typical examples.